2009
DOI: 10.1128/jcm.00510-09
|View full text |Cite
|
Sign up to set email alerts
|

Highly Sensitive Fetal Goat Tongue Cell Line for Detection and Isolation of Foot-and-Mouth Disease Virus

Abstract: A fetal goat cell line (ZZ-R 127) supplied by the Collection of Cell Lines in Veterinary Medicine of the Friedrich Loeffler Institute was examined for susceptibility to infection by foot-and-mouth disease (FMD) virus (FMDV) and by two other viruses causing clinically indistinguishable vesicular conditions, namely, the viruses of swine vesicular disease and vesicular stomatitis. Primary bovine thyroid (BTY) cells are generally the most sensitive cell culture system for FMDV detection but are problematic to prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
88
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(93 citation statements)
references
References 25 publications
5
88
0
Order By: Relevance
“…A previous study 2 confirmed the availability of ZZ-R 127 cells for FMDV isolation using cell culture supernatants and epithelial suspensions. In the current study, the availability was precisely confirmed using samples not evaluated previously.…”
Section: Research-article2013supporting
confidence: 57%
See 4 more Smart Citations
“…A previous study 2 confirmed the availability of ZZ-R 127 cells for FMDV isolation using cell culture supernatants and epithelial suspensions. In the current study, the availability was precisely confirmed using samples not evaluated previously.…”
Section: Research-article2013supporting
confidence: 57%
“…However, the ZZ-R 127 cells are not susceptible to swine vesicular disease virus, which can cause similar clinical signs to FMD. 2 In addition, porcinophilic FMDV strains do not grow well in the ZZ-R 127 cells.…”
Section: Research-article2013mentioning
confidence: 99%
See 3 more Smart Citations